The effect of Lactobacillus reuteri supplementation in Helicobacter pylori infection: a placebo-controlled, single-blind study - Buckley, Martin (BMC Nutr, 2018)
BACKGROUND: Helicobacter pylori is the major cause of chronic gastritis, and considered as a risk factor for peptic ulcer and gastric cancer. The H. pylori standard antibiotic therapy fails in about 25–30% of cases, particularly because of the increasing occurrence of resistance to antibiotics. The aim of the current study was to investigate whether the strain Lactobacillus reuteri DSM17648 which has been previously shown to reduce Helicobacter pylori load additionally improves gastrointestinal symptoms in H. pylori positive subjects when used in a 28 days supplementation. METHODS: In a single-blinded, placebo controlled study 24 H. pylori-positive adults (13 females, 11 males; median age: 43.5) with mild dyspepsia (mean GSRS score: 11.82) received placebo for 28 days followed by Pylopass™ containing the L. reuteri DSM 17648 (2 × 10(10) cells per day) for the following 28 days. After 28 days of Pylopass™ supplementation the change in H. pylori load was measured by (13)C urea breath test ((13)C-UBT) and the change in symptoms were determined by the Gastrointestinal Symptom Rating Scale (GSRS). In addition, blood assessments were conducted to measure the physiological changes relevant in terms of safety. RESULTS: After a 28-day supplementation phase with Pylopass™ there was a trend for reduction of H. pylori load in 62.5% of the subjects and for the overall GSRS scores in 66.7% of subjects. The overall GSRS scores from baseline to day 56 following all 24 subjects undergoing the placebo phase followed by the Pylopass™ phase was significantly decreased (p = 0.005). The mean 13C-UBT δ value decreased by 22.5% during the Pylopass™ supplementation phase (− 3.14), while the mean 13C-UBT δ increased by 37.3% (+ 3.79) in the placebo phase. No side effects were reported in either study phase. CONCLUSION: The results demonstrated that L. reuteri DSM17648 has the potential to suppress H. pylori infection, and may lead to an improvement of H. pylori-associated gastro intestinal symptoms. Further studies with adequate power should be performed. TRIAL REGISTRATION: Clinicaltrials.gov: NCT02051348 (January 30, 2014).